1970
DOI: 10.1161/01.res.26.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Depression of Myocardial Contractility in Rats by Free Fatty Acids during Hypoxia

Abstract: Rat papillary muscles were used to study the influence of glucose (5 HIM), linoleate (1 to 1.75 mMJ, octanoate (0.5 to 1.75 HIM) and pent-4-enoic acid (1 to 5 DIM) on mechanical performance under oxygenated, hypoxic and anoxic conditions. The buffer solution contained 0.3 DIM albumin. Free fatty acids (FFA) (1.0 to 1.75 DIM) did not alter mechanical performance under oxygenated conditions. During hypoxia or anoxia, FFA (0.5 to 1.75 HIM) depressed contractility and increased resting force; glucose improved mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
2

Year Published

1971
1971
1992
1992

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(47 citation statements)
references
References 28 publications
7
38
2
Order By: Relevance
“…Mechanical factors, however, can be ruled out as responsible for the elevated MYO2, as systolic and enddiastolic LVP, dP/dt, CO, and HR remained unchanged during raised plasma-FFA. These results are in accordance with Henderson, Most, Parmley, Gorlin, and Sonnenblick (12) who found that FFA did not alter developed force in well-oxygenated rat papillary muscle.…”
Section: Discussionsupporting
confidence: 92%
“…Mechanical factors, however, can be ruled out as responsible for the elevated MYO2, as systolic and enddiastolic LVP, dP/dt, CO, and HR remained unchanged during raised plasma-FFA. These results are in accordance with Henderson, Most, Parmley, Gorlin, and Sonnenblick (12) who found that FFA did not alter developed force in well-oxygenated rat papillary muscle.…”
Section: Discussionsupporting
confidence: 92%
“…Marked depression of myocardial contractility has been observed in oxygen-limited hearts receiving high concentrations of FFA (11,12). This has been attributed to increased oxygen demand (12), suggesting that FFA in high concentrations contribute to the myocardial cell injury.…”
mentioning
confidence: 99%
“…Although the beneficial effect of glucose is known in isolated hearts during oxygen deprivation and subsequent recovery (19)(20)(21)(22), clinical trials with glucose, potassium, and insulin in patients with acute myocardial infarction have yielded conflicting results (23)(24)(25). However, as pointed out by Owen, Thomas, and Opie (26), and by Henderson, Most, Parmley, Gorlin, and Sonnenblick (27), this treatment has been directed rather towards replacing intracellular potassium than depressing myocardial uptake of FFA through high plasma glucose concentrations. As a result, plasma FFA and myocardial uptake of FFA were not measured in these studies.…”
Section: Discussionmentioning
confidence: 99%